Homocystinuria presenting as a calcified right atrial mass - Tahleel Altaf Shera; Naseer Ahmed Choh; Faiz Altaf Shera; Azher Maqbool Khan (Wolters Kluwer Medknow Publications, 2018)
Homocystinuria is a genetic inborn error of metabolism due to the deficiency of cystathionine β-synthase resulting in increased serum homocysteine and methionine and decreased cysteine which predisposes affected individuals to arterial and venous thromboembolic phenomena. We present a case of homocystinuria who presented to us as a calcified right atrial mass during the evaluation for lower respiratory tract infection. Our case reveals an unusual mix of findings using imaging with multiple detector computed tomography and radiographs.